Projeto didático de leitura e escrita do gênero poema a partir da obra “Felpo Filva” - Sousa, Antonia Albaneide de (2021)
According to Bakhtin (2003 [1979]), speech genres are representations of utterances (oral or written), consisting of thematic content, compositional structure and style. It is understood that working with speech genres in the classroom, it is necessary to think about the theoretical-methodological perspectives to better address them in Portuguese language classes. The general objective of this work is to understand how the work with the poem genre can be accomplished through a didactic project of reading and writing, in dialogue with the literary book. In order to achieve the proposed objective, we specifically seek: a) to elaborate a didactic project of reading and writing poems, in order to include, in addition to working with the genre, a more comprehensive study of reading the book “Felpo Filva” (FURNARI , 2006); b) develop activities that can help students to develop reading and writing skills; c) to characterize how the didactic project elaborated can contribute to the formation and development of the student-reader-writer-critic. Therefore, this work, of bibliographic nature, is located in Applied Linguistics, theoretically based on the conception of language as interaction, according to the assumptions of the Bakhtin’s Circle. (1919-1974), as well as in the studies on reading and writing light of that perspective. Furthermore, the work is theoretically and methodologically anchored in the didactic project of reading and writing gender, proposed by Lopes-Rossi (2002a, 2002b, 2008) and developed by other authors, such as Ohuschi (2018; 2019). The project, presented in this study, is divided into two parts. The first is aimed at reading, step by step, the work “Felpo Filva” (FURNARI, 2006), with indications of how the teacher needs to proceed. The second, presents the didactic modules of reading and writing of the poem genre, with activities that contemplate the context of production, the thematic content, the understanding and interpretation of the text, to which sphere it belongs, the compositional construction and the style, as well as the Writing and circulation module of the genre. Through the elaboration of the project, it appears that this theoretical-methodological approach can enable the teacher to: (a) integrate work with the genre poem and literary text; (b) work gradually, starting from the students' previous knowledge, aiming to develop reading and writing skills; (c) dialogue with the literary text, specifically, with the poem; (d) know the constituent aspects of the poem genre, such as theme, form and style.